Association Between Conflict of Interest and Published Position on Hypoglossal Nerve Stimulation for Sleep Apnea. (August 2021) - Crossley, Jason R.; Wallerius, Katherine; Hoa, Michael; Davidson, Bruce; Giurintano, Jonathan P.
Objective: To determine if there is an association between authors' financial conflict of interest and published position on clinical use of hypoglossal nerve stimulation for obstructive sleep apnea. Study Design: Retrospective cross-sectional analysis. Setting: International roster of authors and articles analyzed. Methods: A Google Scholar search was performed for editorials and reviews citing the 2014 New England Journal of Medicine article on hypoglossal nerve stimulation for obstructive sleep apnea. Included articles were coded as favorable or neutral. Conflict of interest was recorded as declared by the authors in these articles and as independently searched in the Open Payments registry. Results: Sixteen articles from 45 independent authors were analyzed. Nine articles by authors were coded as favorable. Among authors of articles with favorable views, 16 (59%) had a financial conflict of interest with the manufacturer of the hypoglossal nerve stimulator device, as opposed to only 1 of 21 (5%) authors of neutral/unfavorable articles. When we included only authors to whom payments could be identified or excluded on Open Payments, 16 of 20 (80%; 95% CI, 62%-98%) authors of favorable articles had a financial conflict, while 1 of 10 (10%; 95% CI, 0%-29.6%) of neutral/unfavorable articles did ( P = .004). Conclusion: Our study demonstrates an association between published position on hypoglossal nerve stimulator use and financial conflict with the device manufacturer. Several undeclared conflicts were also found, suggesting a role for independent search for conflicts during the review process.